2020
DOI: 10.1002/jnr.24703
|View full text |Cite
|
Sign up to set email alerts
|

Pain‐induced alterations in the dynorphinergic system within the mesocorticolimbic pathway: Implication for alcohol addiction

Abstract: The International Association for the Study of Pain (IASP) defines pain "as an unpleasant sensory and emotional experience associated with actual or potential tissue damage or described in terms of such damage" (IASP Task Force on Taxonomy, 1994). As an emotional experience, pain usually negatively impacts patients' daily lives, not only because of physical impairment but also because of the appearance of neuropsychiatric comorbidities such as depression, anxiety, or even addiction. Because of this complex sit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 147 publications
1
7
0
Order By: Relevance
“…Moreover, the MCLS seems to be involved in the modulation of negative affective states occurring in pain conditions. (Caputi et al, 2019;Jesús David Lorente et al, 2020;Massaly et al, 2019) Thereby, we measured the mRNA levels of pDYN and KOR in the NAc and the Amy by qRT-PCR together with its protein expression in these areas by ELISA and western blot.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the MCLS seems to be involved in the modulation of negative affective states occurring in pain conditions. (Caputi et al, 2019;Jesús David Lorente et al, 2020;Massaly et al, 2019) Thereby, we measured the mRNA levels of pDYN and KOR in the NAc and the Amy by qRT-PCR together with its protein expression in these areas by ELISA and western blot.…”
Section: Resultsmentioning
confidence: 99%
“…Many studies highlighted that pain induces anxiety-and anhedonia-like behaviours as well as low motivation for natural reinforcement under a goal-directed behaviour (Lorente et al, 2020;Markovic et al, 2021;Massaly et al, 2019). However, unfortunately, most of these studies used only male subjects and limited observations only to specific time points after pain induction.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the recent number of reviews on pain, its mechanism, its comorbidities, and potential therapeutics (Garcia-Larrea and Quesada, 2022;Haanpää and Treede, 2022;Hu et al, 2022;Lorente et al, 2022b;Song et al, 2022), the crosstalk between neuroinflammation, opioids and pain remains poorly understood. Nonetheless, numerous in vivo experiments in rats have shown that morphine administration provokes the release of inflammatory mediators in the dorsal horn of the spinal cord, which is a key area in pain management (Johnston, 2004;Bai et al, 2014;Tsai et al, 2016;Eidson and Murphy, 2019).…”
Section: Pain-derived Neuroinflammation: Role Of Morsmentioning
confidence: 99%
“…Moreover, the MCLS seems to be involved in the modulation of negative affective states occurring in pain conditions. (Caputi et al, 2019;Jesús David Lorente et al, 2020;Massaly et al, 2019) Thereby, we measured the mRNA levels of pDYN and KOR in the NAc and the Amy by qRT-PCR together with its protein expression in these areas by ELISA and western blot.…”
Section: Dynorphin/kappa Opioid Receptors Mrna and Protein Levels Alt...mentioning
confidence: 99%